The look-it-up book of explorers - Kimmel, Elizabeth Cody (Random House, 2004)
Examines the lives and achievements of approximately forty explorers from throughout history, looking at excursions to the Americas, Africa, Asia, Australia and the Pacific, the Arctic and Antarctica, outer space, and the deep sea.